Optimización de Sustratos a base de Residuos Orgánicos para la producción de Hongos entomopatógenos: Beauveria bassiana, Lecanicillium lecanii y Metarhizium anisopliae - Díaz Falcón, Carla Elena (2015)
Efficiency of organic substrates for the production of conidia of entomopathogenic fungi was assessed. We used solid substrates using organic waste as whole rice polishing, nelen, husks and ground whole rice, composed of huairuro and papelillo sawdust, ground yellow corn, ground corn cob and peanut shell ground. The best conidial production of Beauveria bassiana is presented in the peanut shell substrate + nelen ground yeast enriched with a concentration of 5.98 x 109 conidia g-1 substrate , for Lecanicillium lecanii presented in the shell substrate Nelen ground + enriched peanut cane molasses getting to have a concentration of 3.43 x 109 conidia g -1 substrate and greater Metarhizium anisopliae conidia production was recorded in the substrate composed of ground peanut shells Nelen + enriched with calcium carbonate with a concentration of 3.3 x 109 conidia g-1 substrate, determining conidia production was done using a Neubauer chamber , where the conidia count was performed and to determine the germination percentage was made using a microscope